PHBS EDUCATION ON HANDWASHING WITH SOAP TO INCREASE AWARENESS OF INFECTIOUS DISEASES - Nursafiah, Nur safiah; Maulina, Meutia; Aswarita, Rika; Adawiyah, Rabiyatul; Ladipin, Ladipin (Universitas Muhammadiyah Aceh, 2024)
Clean and Healthy Living Behavior (PHBS) is a health behavior carried out by a person with individual awareness that can help him from an illness and can become an individual who plays an active role in the health sector in community activities. PHBS needs to be applied to children from an early age so that children understand and are able to apply it in everyday life. This effort must start from instilling a healthy mindset in society which must be started and worked on by oneself. This effort is to realize the highest level of public health as an investment for the development of productive human resources. The aim of the service is to provide an understanding of the importance of healthy living. The method used in this service is face to face. Several stages carried out in this service activity are making plans, delivering material through counseling, hand washing demonstrations, questions and answers, and re-demonstrations. There were 20 participants in this activity at the Kutabaro Village hall building. The research results showed that this service activity ran smoothly, because the support and participation of the participants were quite enthusiastic and active in this activity. This community service activity is able to increase participants' understanding of the importance of PHBS in everyday life. Clean and Healthy Living Behavior (PHBS), especially washing hands using soap and water, has been carried out with steps and demonstration. There were 20 participants in this activity at the Kutabaro Village hall building. The research results showed that this service activity ran smoothly, because the support and participation of the participants were quite enthusiastic and active in this activityKeywords : PHBS, Washing Hands, Infectious Diseases